SÍNTESIS DE LA DEFENSA DE LA LIBRE COMPETENCIA EN EL PERÚ: CONTENIDO Y APLICACIÓN DEL DECRETO LEGISLATIVO N° 1034.- LEY DE REPRESIÓN DE CONDUCTAS ANTICOMPETITIVAS (LRCA) - Stucchi, Pierino (2019)
The purpose of this article is to analyze the main aspects of the provisions of LegislativeDecree No. 1034 - Law on the Repression of Anti-Competitive Conductsand the recent amendments introduced by Legislative Decree No. 1205. The substantiveaspects are outlined, such as the scope of the subjective application, theterritorial scope, the prohibited conducts and the legal consequences. The proceduralaspects are also pointed out, mainly, the procedural instruments with whichthe competition agency has to ensure effective competition in the market, as wellas the possibilities allowed by the termination commitment, the leniency programand the procedure of exoneration from sanction, as well as corrective measuresin its two modalities.